Sosialisasi Olahraga Pickleball Bagi Guru PJOK Sekolah Dasar di Kota Cimahi - Hambali, Sumbara; Hidayat, Yudi; Paembonan, M Saleh; Hardi, Veny Juniarni; Bernhardin, Dindin (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Lack of physical activity among PJOK Elementary School teachers is an important problem to study and overcome. Besides that, the process of providing only the same material (monotonous) makes students tend to be reluctant to carry out physical activities. Of course, if this is left unchecked, it will seriously endanger the growth and development of the students themselves, as well as the views or image of PJOK teachers, which will have an unfavorable impact. One solution is to introduce new sports which are currently on the rise and are widely practiced in several areas. Based on these problems, we as academics in the field of physical education need to provide knowledge and information about new types of sports that are currently popular with many people in all circles, and one of them is introducing the sport of Pickleball. Some of the implementation methods for this activity are delivery using lecture, discussion and question and answer methods, as well as direct demonstrations or practice. This research was carried out at the Mandiri 5 Elementary School in Cimahi City, involving one regional branch of Central Cimahi City with a total of 8 schools involved. The results of this research show that what is proposed in this community service activity plan can be implemented well and fulfilled. From the results of the implementation of this activity, it was found that the majority of PJOK teachers in the Central Cimahi area were still unfamiliar with the sport of pickleball, so they had quite high enthusiasm for learning about the sport of pickleball.